Pengaruh Pendidikan Orang Tua terhadap Sikap Disiplin Tata Tertib Siswa Kelas VI di SD Negeri 24 Banda Aceh - Sahnaz Marlianda; Ahadin Ahadin; Said Darnius (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2023)
Education is a shared responsibility, namely family, community and school. The family is a child's first educational institution. Parents play an important role in shaping their children, including developing a disciplined attitude. This study is entitled, "The Influence of Parental Education on Discipline Attitudes of Class VI Students at SD Negeri 24 Banda Aceh." The formulation of the problem in this study is to reveal "Does parental education have a significant effect on the discipline attitude of class VI students at SD Negeri 24 Banda Aceh?" The methodology used in this study is a quantitative approach with related research methods. The study was conducted at SD Negeri 24 Banda Aceh with a sample of 40 Class VI students. Data collection techniques using closed-ended questionnaires with Likert scales. Data analysis techniques used product-moment correlation tests, and hypothesis testing was performed using t-tests at a significance level of 5% (0.05) The results of the study showed that parental education and student disciplinary attitudes had a correlation value of (0.771) included in the strong category by contributing to the influence of parental education with 59.5% disciplinary attitude of class VI students. The results of testing the hypothesis obtained t-count 7.474, this indicates that t-count (7.474) t-table (2.021) therefore it can be concluded that Ho is rejected, and Ha is accepted. Thus the conclusion obtained is that there is a significant influence of parents on the disciplinary attitude of class VI students at SD Negeri 24 Banda Aceh.Keywords :  Parent Education, Discipline attitude, Students